2017
DOI: 10.1097/ijg.0000000000000766
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy and Complications of Cyclophotocoagulation and Second Glaucoma Drainage Device After Initial Glaucoma Drainage Device Failure

Abstract: Although both second procedures are efficacious in lowering IOP and number of IOP-lowering medications, TSCPC failed earlier, whereas a second GDD had significantly more complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 11 publications
2
21
0
1
Order By: Relevance
“…Based on our findings, and supported by previously published literature, in patients with residual visual acuity, both a second glaucoma drainage device implantation or cyclodestructive procedure may be useful in reducing IOP with a sufficient safety profile [15,33,34]. The results of the running randomized clinical trial of the American Glaucoma Society (AGS): Second Aqueous Shunt Implant versus Transscleral Cyclophotocoagulation Treatment Study (ASSISTS, NCT02691455), might indicate the better treatment option after a first failed tube implant.…”
Section: J Clin Med 2020 9 2039 8 Of 12supporting
confidence: 74%
“…Based on our findings, and supported by previously published literature, in patients with residual visual acuity, both a second glaucoma drainage device implantation or cyclodestructive procedure may be useful in reducing IOP with a sufficient safety profile [15,33,34]. The results of the running randomized clinical trial of the American Glaucoma Society (AGS): Second Aqueous Shunt Implant versus Transscleral Cyclophotocoagulation Treatment Study (ASSISTS, NCT02691455), might indicate the better treatment option after a first failed tube implant.…”
Section: J Clin Med 2020 9 2039 8 Of 12supporting
confidence: 74%
“…Although the power of the study was inadequate for the statistical analysis of postoperative complications, eyes in the CPC group had fewer serious adverse events. In a similar retrospective study, Wang et al [ 41 ] recently examined the efficacy and safety of a second glaucoma drainage device ( n = 35) versus transscleral CPC ( n = 40) following failure of a previous drainage device. The authors found that although both groups achieved significant IOP reduction, eyes implanted with a second drainage device had longer mean survival time (45.0 months) than eyes treated with CPC (26.5 months), but they suffered significantly more postoperative complications (60% versus 20% of eyes) [ 41 ].…”
Section: Techniques and Evidence On Efficacymentioning
confidence: 99%
“…Despite being a second AGV implantation, our success rates are comparable to that of initial AGVs in current literature. is could reflect the long-term efficacy of a second FP7 AGV as a treatment option following a failed first GDD, as supported by Levinson et al [10,11]. Several other studies have also evaluated the outcomes of second GDDs in general (not confined to AGV implants).…”
Section: Discussionmentioning
confidence: 91%
“…Shah et al reported that additional tube shunt has better IOP control than tube shunt revision by excision of an encapsulated bleb [9]. Levinson et al demonstrated that while both second GDDs and cyclodestructive procedures effectively reduce IOP after a failed primary GDD, a second GDD had better long-term success rates [10,11].…”
Section: Introductionmentioning
confidence: 99%